Application of foliar biofertilizers with and without NPK in cultivating white-glutinous corn - Roselyn R. Adajar; Erma C. Taer (Future Science, 2021)
Organic farming used fermented fruit and plant juices as foliar fertilizers to enhance crop production. However, the usage is usually limited to sole fruit or plant fermentation with chemicals and other growth enhancers. The use of various fruits, plants, fish products, and Cyanobacteria with Mycorrhizal fungi combinations to enhance white-glutinous corn has not yet been explored. This trial investigated the different fermented fruits (FFJ), plants (FPJ), fishes (FAA), and commercial Cyanobacteria with Mycorrhizal fungi (Rhizocote) in single-use or combination with NPK to enhance the growth, yield, and Return on Investment (ROI) of cultivating white-glutinous corn. The application was 2 tbsp L-1 water for single use of fermented biofertilizers while 1 tbsp L-1 water for fermented foliar with NPK combinations. The results showed that the height of corn was not significant among treatments in 30 and 60 days after planting (DAP). However, corn treated with Rhizocote alone was the tallest in 45 DAP and had longer days to reach 50% corn tasseling. White-glutinous corn treated with Rhizocote + NPK had the highest number of ears. The rest of the treatments yielded a comparable number of ear sizes ranging from 1.27 to 1.37 cm. The highest yield of marketable green ears accounted for 7.45 t ha-1 with Rhizocote + NPK, while the lowest was observed when the white-glutinous corn was fertilized alone with FFJ at 2.93 t-ha. The Rhizocote + NPK obtained the highest R.O.I. of 263.68% compared to other treatments. Thus, the recommendation is to use 1.00 tbsp L-1 water commercial Rhizocote + recommended NPK for a productive and profitable white-glutinous corn. More investigation using different agri-fishery products fermentation at higher concentrations are needed in culture of white-glutinous corn for green ear production in various planting season.